Rationale Behind Targeting Fibroblast Activation Protein–Expressing Carcinoma-Associated Fibroblasts as a Novel Chemotherapeutic Strategy - Brennen, W. Nathaniel (2012)
The tumor microenvironment has emerged as a novel chemotherapeutic strategy in the treatment of cancer. This is most clearly exemplified by the antiangiogenesis class of compounds. Therapeutic strategies that target fibroblasts within the tumor stroma offer another treatment option. However, despite promising data obtained in preclinical models, such strategies have not been widely used in the clinical setting, largely due to a lack of effective treatments that specifically target this population of cells. The identification of fibroblast activation protein α (FAP) as a target selectively expressed on fibroblasts within the tumor stroma or on carcinoma-associated fibroblasts led to intensive efforts to exploit this novel cellular target for clinical benefit. FAP is a membrane-bound serine protease of the prolyl oligopeptidase family with unique post-prolyl endopeptidase activity. Until recently, the majority of FAP-based therapeutic approaches focused on the development of small-molecule inhibitors of enzymatic activity. Evidence suggests, however, that FAP’s pathophysiological role in carcinogenesis may be highly contextual, depending on both the exact nature of the tumor microenvironment present and the cancer type in question to determine its tumor-promoting or tumor-suppressing phenotype. As an alternative strategy, we are taking advantage of FAP’s restricted expression and unique substrate preferences to develop a FAP-activated prodrug to target the activation of a cytotoxic compound within the tumor stroma. Of note, this strategy would be effective independently of FAP’s role in tumor progression because its therapeutic benefit would rely on FAP’s localization and activity within the tumor microenvironment rather than strictly on inhibition of its function.